Perspectives, Expectations, and Concerns of European Patient Advocates on Advanced Therapy Medicinal Products - Benvenuti, Stefano; Wang, Chiuhui Mary; Borroni, Simona (Frontiers in Medicine, 2021)
This paper presents the results of a qualitative study based on semi-structured interviews of 10 expert patient advocates on several different issues around Advanced Therapy Medicinal Products (ATMPs). The interviews were conducted between February and May 2020 based on a guideline with a list of 8 topics that covered concerns about safety and ethics, access problems and limitations, pricing of ATMPs and educational needs for patient communities. Overall, the interviewees expressed a high degree of convergence of opinions on most of the topics and especially on the identification of the reasons for concern. Conversely, when asked about possible solutions, quite a wide range of solutions were proposed, although with many common points. However, it highlights that the debate is still in its infancy and that there are not yet consolidated positions across the whole community. A general concern emerging from all the interviews is the potential limitation of access to approved ATMPs, both due to the high prices and to the geographical concentration of treatment centers. However, patients recognize the value of a model with a limited number of specialized clinical centers administering these therapies. On the ethical side, patients do not show particular concern as long as ATMPs and the underlying technology is used to treat severe diseases. Finally, patients are asking for both more education on ATMPs as well as for a more continuous involvement of patient representatives in the whole “life-cycle” of a new ATMP, from the development phase to the authorization, from the definition of the reimbursement scheme to the collection of Real Word Data on safety and long-term efficacy of the treatment.